Activating Hope in the Midst of Crisis: Emotions, Transformative Learning, and "The Work That Reconnects". (October 2017) - Hathaway, Mark D.
Joanna Macy's "Work that Reconnects" (WTR) is a transformative learning process that endeavors to help participants acknowledge, experience, and understand the emotions that may either empower or inhibit action to address the ecological crisis. The WTR seeks to work through grief, fear, and despair to animate a sense of active, empowering hope rooted in gratitude, compassion, imagination, community, and collective action. Drawing on theoretical perspectives from neuroscience, ecopsychology, and transformative learning, this paper analyzes how emotions may either impede or facilitate active engagement in ecological issues. The assumptions, goals, and process of the WTR are then presented in light of these insights. Finally, a case study involving the use of the WTR with young adults along with their reflections on the experience are considered to illustrate how the process may be employed as well as to analyze some of the benefits, challenges, and limitations of using this transformative learning process.